Local Environment of Terbium(III) Ions in Layered Nanocrystalline Zirconium(IV) Phosphonate–Phosphate Ion Exchange Materials - Terban, Maxwell W; Shi, Chenyang; Silbernagel, Rita; Clearfield, Abraham; Billinge, Simon J. L (Inorganic chemistry, 2017)
The structures of Zr(IV) phosphonate-phosphate based, unconventional metal organic framework materials have been determined using atomic pair distribution function analysis of high energy, X-ray total scattering diffraction data. They are found to form as nanocrystalline layers of Zr phosphate, similar to the bulk, but with a high degree of interlayer disorder and intermediate intralayer order extending around 5 nm. These materials are of interest for their high selectivity for 3+ lanthanide ions. To investigate the mechanism of the selectivity, we utilize difference pair distribution function analysis to extract the local structural environment of Tb3+ ions loaded into the framework. The ions are found to sit between the layers in a manner resembling the local environment of Tb in Scheelite-type terbium phosphate. By mapping this local structure onto that of the refined structure for zirconium-phenyl-phosphonate, we show how dangling oxygens from the phosphate groups, acting like nose hairs, are able to reorient to provide a friendly intercalation environment for the Tb3+ ions.